EKSPLORASI ETNOMATEMATIKA BENTUK ANYAMAN DAUN LONTAR KEBUDAYAAN LAMAHOLOT - Maria nirmala hospa Gawen; Gregorius Taga; Konstantinus Denny Pareira Meke (Program Studi Pendidikan Matematika, 2021)
Mathematics studied in school is abstract and has no benefit in their life or culture, so mathematics is hard for students to understand. However, students do not realize that mathematical concepts have applied in everyday life. Ethnomathematics is an approach that links mathematics and culture very closely. One of them is a form of woven motifs made of palm leaves that is related to mathematical concepts. This study aims to: 1) Identify the motives found in palm leaf matting in the Lamaholot culture. 2) Knowing the relationship between palm leaf woven motifs in the Lamaholot culture with mathematics learning in schools. The research method used is qualitative with an ethnographic approach. Data collection used observation, interviews and documentation. The data analysis techniques used were observation, interview and documentation. The results showed that the woven motif of palm leaves has a relationship with mathematics. In the woven motif of palm leaves in the form of a flat geometric shape, the dese woven motif has a rhombus plane geometric shape and osan has a parallelogram geometric shape, the sebeng and sodong woven motifs have an isosceles triangle flat geometric shape and the woven klekar motif has a shape hexagon plane geometry. But the people in Atawai Village do not know that the culture they apply and use is related to learning mathematics.